Association of Metabolic Dysfunction-Associated Fatty Liver Disease With Left Ventricular Diastolic Function and Cardiac Morphology - Peng, Dandan; Yu, Zhenqiu; Wang, Mingwei; Shi, Junping; Sun, Lei; Zhang, Yuanyuan; Zhao, Wenbin; Chen, Chen; Tang, Jiake; Wang, Chunyi; Ni, Jie; Wen, Wen; et al. (Frontiers in Endocrinology, 2022)
Background &Aim: Non-alcoholic fatty liver disease (NAFLD) is closely related with cardiovascular diseases (CVD). A newly proposed definition for metabolic dysfunction-associated fatty liver disease (MAFLD) change from NAFLD. The clinical effect of this change on abnormalities of cardiac structure and function is yet unknown. We aimed to examine whether MAFLD is associated with the left ventricular (LV) diastolic dysfunction and cardiac remolding, and further identify the impact of different subgroups and severity of MAFLD. Method: We evaluated 189 participants without known cardiovascular diseases. Participants were categorized by presence of MAFLD and normal group. Then, patients with MAFLD were sub-classified into three subgroups: MAFLD patients with diabetes (diabetes subgroup), overweight/obesity patients (overweight/obesity subgroup) and lean/normal weight patients who combined with two metabolic risk abnormalities (lean metabolic dysfunction subgroup). Furthermore, severity of hepatic steatosis was assessed by transient elastography (Fibroscan®) with controlled attenuation parameter (CAP), and patients with MAFLD were divided into normal, mild, moderate and severe MAFLD groups based on CAP value. Cardiac structure and function were examined by echocardiography. Results: Compared to normal group, LV diastolic dysfunction (LVDD) was significantly more prevalent in the MAFLD group (31.9%vs.52.8%, P=0.018). Overweight subgroup and diabetes subgroup were significant associated with signs of cardiac remolding, including interventricular septum thickness, LV posterior wall thickness, left atrial diameter (all P＜0.05), relative wall thickness, and left ventricular mass index (all P＜0.05). Additionally, moderate to severe MAFLD patients had higher risks for LV diastolic dysfunction and cardiac remolding (all P value＜0.05). Conclusion: MAFLD was associated with LV diastolic dysfunction and cardiac remolding, especially in patients with diabetes, overweight and moderate to severe MAFLD patients. This study provides theoretical support for the precise prevention of cardiovascular dysfunction in patients with MAFLD.